Адская рулетка: [роман] / Леонид Влодавец - Влодавец Л. И. (Черная кошка, 1997)
Экземпляры: аб. (2009) / Инвентарный номер: 52717 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 588 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44